Histological features of oral cavity mucous membrane epithelium in six-month-old experimental animals born with macrosomia - Garmash, Olga; Gubina-Vakulik, Galina; Vondrášek, David (Acta Medica, 2018)
We examined the histological features of the mucobuccal fold of oral cavity mucous membrane from the area of the masticatory teeth roots' projection in 6-month-old Wistar Albino Glaxo rats with fetal macrosomia. The animals were divided into groups according to the body weight, the body length, and the Quetelet index at birth. A morphological study was performed using the Leica SP8 AOBS laser scanning confocal microscope and a conventional light (Axiostar, Zeiss) microscopy. Morphometric parameters were used to estimate the degree of acanthosis development in the epithelium of the oral mucosa, which indicates the intensity of its proliferation. Numerous narrow and deep acanthotic outgrowths and densely located 'juvenile' epitheliocytes in the basal layer on the apex of the acanthotic protrusions were found in animals with fetal macrosomia that was due to intrauterine obesity. In these animals, the morphometric index, which we used, was maximally different from that in the control group. In animals with fetal macrosomia that was due to intrauterine growth acceleration of the body, the hyperproliferation of the mucous membrane epithelium of the oral cavity was absent or little pronounced. It can be assumed that fetal macrocosmia with obesity causes instability in the epithelium of the oral cavity mucosa, its rapid death, and therefore, a more active stimulation of proliferation.
Keywords: makrosomie plodu; krysa rodu Rattus; Animals; epitel; Epithelium; zvířata; Microscopy, Confocal; konfokální mikroskopie; Rats, Wistar; ústní sliznice; Fetal Macrosomia; Mouth Mucosa; Rats; potkani Wistar